Ressignificações contemporâneas dos imaginários racializados nas artes visuais - Meirinho, Daniel (Farol, 2021)
This article analyses how counterstrategies of representational contestation by contemporary black visual artists can subvert the negative racial stereotypes created and consolidated in the visual arts. Drawings, paintings, and racial photographs continue to make up the imaginary and teaching materials, school curricula in arts and history applied throughout the country. The process of signifying the racialized visual imaginary of colonial control images amplifies complexities of Afro-Brazilian culture and redefines imaginative narratives that have been reiterated until today. This work aims to identify how modes of transcodification and resistance in contemporary visual productions reinscribe reductionist meanings from decolonial black aesthetic strategies in the arts as transformative praxis and racial questioning.